Polar Research and the Secrets of the Arctic - Pedersen, Torbjørn (Arctic Review on Law and Politics, 2019)
The advantages that some military establishments have enjoyed in the remote Arctic region are diminishing. The military secrets of the Arctic Ocean are being progressively uncloaked, as civilian polar research expands into areas previously known only to a few. This study examines the security ramifications of broadened international research into what has been the most inhospitable and exclusive operational area on Earth. Firstly, the study argues that successful military operations in the Arctic depend on extended knowledge about area-specific issues related to e.g. the upper atmosphere and magnetosphere, weather, sea ice, ocean structure and dynamics, seafloor bathymetry and sediments, as well as reliable target detection systems. Secondly, it finds that a number of nations, both Arctic and non-Arctic, have stepped up their polar research in recent years. Secrets once held by a few are now accessible to many through international cooperation, data-sharing and open-access publishing. Finally, the study concludes that knowledge proliferation is likely to level the Arctic battlefield. Lending terms from Mica Endsley’s three-level Situation Awareness model, polar research will result in increasingly shared perceptions about the Arctic operational environment, contribute to a more uniform comprehension of the elements, and even enable new actors to project a future state of the Arctic environment.